Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1073/pnas.80.4.1111
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide and deduced amino acid sequences of Torpedo californica acetylcholine receptor gamma subunit.

Abstract: The nucleotide sequence has been determined of a cDNA clone that codes for the 60,000-dalton y subunit of Torpedo californica acetylcholine receptor. The length of the cDNA clone is 2,010 base pairs. The 5' and 3' untranslated regions have respective lengths of 31 and 461 base pairs. Data suggest that the putative polyadenylylation consensus sequence A-A-T-A-A-A may not be required for polyadenylylation of the mRNA corresponding to the cDNA clone described in this study. From the DNA sequence data, the amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
187
0
10

Year Published

1984
1984
2007
2007

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(214 citation statements)
references
References 43 publications
17
187
0
10
Order By: Relevance
“…Aligned amino acid sequences of the mouse (LaPolla, Mixter-Mayne, and Davidson, 1985;Isenberg, Mudd, Shah, and Merlie, 1986;Yu, Lapolla, and Davidson, 1986;Gardner, 1990), Torpedo (Noda, Takahashi, Tanabe, Toyosato, Furutani, Hirose, Asai, Inayama, Miyata, and Numa, 1982;Claudio, Ballivet, Patrick, and Heinemann, 1983;Noda, Takahashi, Tanabe, Toyosato, Kikyotani, Hirose, Asai, Takashima, Inayama, Miyata, and Numa, 1983), and Xenopus M2 regions (Baldwin, Yoshihara, Blackmer, Kintner, and Burden, 1988). Amino acids are given by the single letter code.…”
Section: Mousementioning
confidence: 99%
“…Aligned amino acid sequences of the mouse (LaPolla, Mixter-Mayne, and Davidson, 1985;Isenberg, Mudd, Shah, and Merlie, 1986;Yu, Lapolla, and Davidson, 1986;Gardner, 1990), Torpedo (Noda, Takahashi, Tanabe, Toyosato, Furutani, Hirose, Asai, Inayama, Miyata, and Numa, 1982;Claudio, Ballivet, Patrick, and Heinemann, 1983;Noda, Takahashi, Tanabe, Toyosato, Kikyotani, Hirose, Asai, Takashima, Inayama, Miyata, and Numa, 1983), and Xenopus M2 regions (Baldwin, Yoshihara, Blackmer, Kintner, and Burden, 1988). Amino acids are given by the single letter code.…”
Section: Mousementioning
confidence: 99%
“…Work from this laboratory has elucidated the primary structures of all four subunits of the Torpedo californica acetylcholine receptor by cloning and sequencing cDNAs encoding the respective subunit precursors [4 -61; cDNA sequences for the y subunit precursor of the T. californica receptor [7] and the M subunit precursor of the Torpedo marmorata receptor [8, 91 have also been reported by other groups. The conspicuous amino acid sequence homology found among the four subunits of the T. calijornica receptor suggests that the genes encoding them have been generated from a single common ancestor by gene duplications.…”
mentioning
confidence: 99%
“…Changeux et al, 1984). All four ACh receptor subunits are transmembrane polypeptides (Froehner, 198 1;Strader and Rafferty, 1980;Strader et al, 1979;Tarrab-Hazdai et al, 1978;Wennogle and Changeux, 1980) and the complete amino acid sequences of all four subunits have been deduced from the nucleotide sequences of cDNA clones (Claudio et al, 1983;Devillers-Thiery et al, 1983;Noda et al, 1982Noda et al, , 1983a. Reconstitution of the purified ACh receptor in lipid vesicles (Anholt et al, 1981(Anholt et al, , 1982Changeux et al, 1979;Gonzalez-Ros et al, 1980;Huganir et al, 1979;Lindstrom et al, 1980;Wu and Raftery, 1979) and in lipid bilayers (Boheim et al, 1981;Labarca et al, 1984a, b;Nelson et al, 1980;Schindler et al, 1984;Tank et al, 1983) demonstrated that the a,&6 structure is sufjicient to express the transduction of ligand binding into the opening of a cation-specific channel.…”
mentioning
confidence: 99%